Lactose-free hypoallergenic buffalo, goat and sheep milk (Research, Society and Development, 2022)
In the broad society there are metabolic disorders that prevent some people from ingesting cow's milk. This is because certain individuals manifest some food-related pathology, such as allergy to milk proteins and/or lactose intolerance. These pathologies can cause unpleasant effects after the ingestion. Since the compositions of milk from different species have differences in its constituents, it is possible and /or even desirable for people with cow's milk protein allergy condition to consume milk from other species, such as buffalo, goat and sheep as these milks are hypoallergenic. The production of non-bovine milk has been increasing over time, which is an important factor, as it allows the food industry to develop innovative products. Turning milk from buffalo, goat and sheep into a lactose-free product is a way of making milk and dairy products accessible to people who are lactose intolerant. In view of this, the hypoallergenic lactose-free milks of buffalo, goat and sheep origin can reach a part of the public, thus enabling a huge range of innovative products and technologies.